Agricultural Extension Information Sharing Portal - Ebenezer, Omotoso Ayodele (2010)
Extension workers play a major role in information sharing between the ministry and farmers (clientele) in information links and feedback. Information sharing portal is a device in ICT that used to improve efficiency and effective sharing of information between the ministry and extension agents which will in turn serve as technology transfer to the farmers. This research work addressed the objectives of requirement gathering, designing and development of an extension information sharing portal system. System development research method was used. The prototype of information sharing portal was developed with the use of ASP.Net (Microsoft Visual Studio 2008) and Microsoft SQL Server 2008. Five people tested the usability of prototype. The developed portal brings about timely information delivery from ministry to the farmers through extension workers and vice versa. With the use of this device, positive turnaround will manifest in Nigerian rural livelihood and increase in income level.